Test The Antibacterial Effectiveness of Ginger Juice (Zingiber officinale Rosc. Var Rubrum) Against Food Pathogen Bacteria - Dessyre M Nendissa; Sandriana J Nendissa (Pattimura University Ambon Maluku Indonesia, 2021)
The use of very dangerous chemicals for food reservations is still happening in Indonesia. To overcome this problem, it is necessary to have public awareness of the importance of food safety and health, causing the use of synthetic preservatives to be avoided and switching to natural preservatives, one of which is ginger (Zingiber officinale Rosc. Var Rubrum). Ginger contains gingerols which have activities such as antioxidant, antibacterial, anti-inflammatory, anticarcinogenic, antimutagenic, and antitumor. The content of secondary metabolites contained in ginger rhizome plants is an antimicrobial group of phenols, flavonoids, terpenoids, and essential oils contained in the ginger extract and is a group of bioactive compounds that can inhibit microbial growth. The purpose of the study was to determine the antibacterial effectiveness of ginger juice (Zingiber officinale Rosc. Var Rubrum) against food pathogenic bacteria. The results obtained were that at a concentration of 25% it could not inhibit Salmonella Typhimurium and Staphylococcus aureus bacteria, while at concentrations of 50%, 75%, and 100% it could inhibit Salmonella Typhimurium and Staphylococcus aureus bacteria with inhibition zone criteria from moderate to very strong. The greater the concentration of ginger juice given, the greater the inhibition zone obtained.